Implementation of Community Relations as a CSR Strategy of PT. Panca Amara Utama Banggai - Shela Divana Dewi; Suanti Tunggala (Jogjakarta Communication Conference (JCC), 2026)
This study aims to reveal community relations as a Corporate Social Responsibility (CSR) strategy at PT. Panca Amara Utama (PAU). This study uses a qualitative research method. The data collection techniques used are interviews and documentation methods. Community engagement at PT. Panca Amara Utama (ESSA) is based on participation, transparency, respect for local culture, and tangible benefits for the community. An adaptive and dialogue-based approach strengthens the social licence to operate, which is very important in areas with strong cultural and environmental identities such as Banggai. In implementing Corporate Social Responsibility (CSR) programs, PT. Panca Amara Utama (PAU) technically cooperates with offices in Banggai Regency to conduct assessments, identify groups, educate the public, and plan empowerment programs aimed at community groups that have been registered with the relevant offices.